Bacillin 20, a bacterial derived compound, improves soybean growth, photosynthesis and nutrients content under drought stress conditions - Hamid Reza Eisvand; Donald L. Smith (PLoS ONE, 2025)
Water scarcity is a global challenge with profound implications, particularly for agriculture, where it undermines crop production by diminishing yields and heightening vulnerability to environmental stresses. This study investigates the impact of Bacillin 20, a derivative of Bacillus thuringiensis , on soybean plant physiology under drought stress, focusing on growth dynamics, photosynthetic activity, and nutrient assimilation. The experimentation was carried out using a factorial structure within a completely randomized design and four replications. Factors included drought levels (control, −0.75 MPa and −1.5 MPa) and Bacillin 20 concentrations (0, 10 −11 M and 10 −9 M). Results indicated that drought stress significantly reduced plant height, leaf area, shoot dry weight, photosynthetic rate, stomatal conductance, transpiration, substomatal CO 2 concentration, nodulation, and root length and volume. Bacillin 20 application had mixed effects, with no significant impact on plant height but increasing leaf area, enhancing shoot dry weight under moderate drought, and improving photosynthetic rate. The interaction between drought and Bacillin 20 was significant, particularly in terms of shoot dry weight and photosynthetic rate. Additionally, Bacillin 20 at 10 −11 M increased root tips by 12.6% and shoot dry weight by 28%; it increased nodule number by 51% only under normal moisture conditions, and decreased it under drought stress. Drought increased leaf N, Mg, Zn, Fe, Mn, and B contents, while Bacillin raised leaf N at −0.75 MPa and decreased Zn and Mn under severe drought (−1.5 MPa). The increased plant N and decreased nodulation under drought suggest enhanced nodule efficiency. Bacillin 20 did not affect P, K, Ca, and S contents, which were influenced solely by drought.